2014
DOI: 10.1590/s1679-78252014001000005
|View full text |Cite
|
Sign up to set email alerts
|

Study of anisotropic mechanical properties for aeronautical PMMA

Abstract: For the properties of polymer are relative to its structure, the main purpose of the present work is to investigate the mechanical properties of the aeronautical PMMA which has been treated by the directional tensile technology. Isodyne images reveal the stress state in directional PMMA. And then, an anisotropic mechanical model is established. Furthermore, all mechanical parameters are measured by the digital image correlation method. Finally, based on the anisotropic mechanical model and mechanical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…At this strain rate, the yield stress of the PMMA matrix was calculated as 188.5 MPa, which was in good agreement with other studies reporting values of 167 and 174 MPa 49,50 . The Young's modulus of the PMMA matrix was also calculated as 2.82 GPa, falling in the range of 2.07–6.20 GPa at room temperature (300 K), and this was consistent with the literature 51–53 . These results indicated that the ReaxFF force field was suitable for simulating the mechanical properties of the PMMA system and the set parameters were reasonable.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…At this strain rate, the yield stress of the PMMA matrix was calculated as 188.5 MPa, which was in good agreement with other studies reporting values of 167 and 174 MPa 49,50 . The Young's modulus of the PMMA matrix was also calculated as 2.82 GPa, falling in the range of 2.07–6.20 GPa at room temperature (300 K), and this was consistent with the literature 51–53 . These results indicated that the ReaxFF force field was suitable for simulating the mechanical properties of the PMMA system and the set parameters were reasonable.…”
Section: Resultssupporting
confidence: 89%
“…49,50 The Young's modulus of the PMMA matrix was also calculated as 2.82 GPa, falling in the range of 2.07-6.20 GPa at room temperature (300 K), and this was consistent with the literature. [51][52][53] These results indicated that the ReaxFF force field was suitable for simulating the mechanical properties of the PMMA system and the set parameters were reasonable. We also performed tensile simulations for the Ti 2 C/PMMA and Ti 3 C 2 /PMMA nanocomposites at the same strain rate, and the stressstrain curves are also presented in we conducted simulations to analyze the distribution of volume strain and atom density during the tensile process, as shown in Figures 5 and 6.…”
Section: Tensile Propertiesmentioning
confidence: 73%
“…The fracture mechanical properties depend on the molecular chain structures. Therefore, the isotropic mechanical model is unable to describe the mechanical properties of oriented PMMA [17].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, fatigue properties of PMMA were studied primarily based on the isotropic assumption. The author has proposed an anisotropic mechanical model for directional PMMA [12]. This research tracked the growth of fatigue cracks in directional PMMA by a stroboscopic method.…”
Section: Introductionmentioning
confidence: 99%